The Effect of Physical Education Learning Models on Students' Learning Behavior - Sinung Nugroho; Agustin Sastrawan Harahap; Albadi Sinulingga; Budi Valianto; Suprayitno Suprayitno (IKIP PGRI Bojonegoro, 2026)
The purpose of this research is to prove the influence of learning models on students' learning behaviors. The research method used is quantitative research. The research sample consists of 30 people. Data analysis uses independent sample t-test. The test results prove that the learning model has a significant effect on students' learning behaviors, namely learning motivation and student attitudes. The average score before and after learning is significantly different and has experienced an increase.